OPTIMASI PERAWATAN SUMP PIT PUMP P-1205 D UNTUK REPROCESSING CRUDE OIL - Veny Selviyanty; Sir Anderson (Research Center University of Pahlawan Tuanku Tambusai, 2018)
To improve the performance of the pump needs maintenance, system Maintenance is a process carried out to maintain reliability, availability and the ability to maintain equipment or machinery. An effective and efficient maintenance program will support increased production system productivity. But often maintenance programs ignore the actual needs of equipment or machines. To obtain an effective and efficient maintenance program and in accordance with machine requirements, a maintenance center based on reliability, Maintenance Center (RCM) is a risk-based systematic analysis to create an accurate, focused and optimal maintenance method with the aim of achieving optimal reliability. from assets. RCM studies have been carried out on rotary machines, especially pumps, in the oil and gas processing industry. The study was conducted by following the seven steps of RCM, including the determination of the scope of study, Failure Mode and Effect Analysis, Logic Tree Analysis and determination of maintenance strategies. Risk analysis based on the risk matrix is arranged through the consensus of all stakeholders. The risk matrix covers occurrences, detection, and the level of risk (severity) in the economic (economy) aspects of health and safety (health & safety), environment (environment). Furthermore, Risk Priority is calculated based on this risk matrix. Number (RPN). Based on the values of RPN and Logic Tree Analysis, a maintenance strategy was prepared for each type of failure mode. This study has also succeeded in establishing a better maintenance strategy for Sump Pit pumps which is then used as the basis for the preparation of a new maintenance program.